Community pharmacists' perception and exposure to drug promotion in Pakistan: a cross-sectional study. Issue 1 (31st January 2022) - Gillani, Ali Hassan; Zhao, Mingyue; Hussain, Azzah Khadim; Munir, Kiran; Masood, Shamaila; Saeed, Amna; Fang, Yu
Abstract : Objective: Drug promotion is a factor that promotes the irrational use of drugs and sometimes negatively influences the prescribing/dispensing pattern. So there was a need to assess the views about accepting gifts and attitudes/influence towards drug promotion among community pharmacists in Punjab, Pakistan. Setting: Adopting a preused questionnaire, we conducted a cross-sectional multiple-site survey study. We distributed questionnaires to pharmacists in the community pharmacies to investigate the exposure, scepticism and acceptance to drug promotion as well as their perception about the appropriateness of gifts and to check if they had been taught about dealing with medical representatives. Data were analysed in simple percentages, and the χ 2 test was used to evaluate association with demographics. All the analysis was done using SPSS V.23.0. Results: A total 86.9% (463/533) pharmacists completed the survey. One out of four pharmacists reported being taught about the ethics of drug promotion (26.8%) and about how to interpret drug promotional material (25.0%) and were significantly associated with higher age (age 31%–35 years, 81.9%; p<0.05). More than two-thirds of the respondents found it appropriate to accept stationery (73.4%) and textbooks (70.6%) as gifts, and only 17.5% felt it was appropriate to accept direct money. Less than half of the pharmacists (47.3%) perceived drug companies were useful for gaining knowledge about new drugs. Majority (76.2%) thought these drug promotions play a role in the irrational prescribing of antibiotics and 18.6% dispensed antibiotics due to these promotions. Conclusion: The majority of pharmacists participating in this study felt it was appropriate to receive small value gifts from pharmaceutical companies. Only a small proportion of the respondents was given ethical training and education about drug promotion. Improving the syllabus and updating the pharmacist's knowledge after graduation, as part of continued pharmacy education, will eventually improve the healthcare professionals' capability to act for the patients' welfare.